(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The aim of the research was to identify "the level of availability of requirements for using information and communication technology from the point of view of faculty members at the Libyan Academy for Postgraduate Studies, Khoms Branch", and to achieve the aim of the research, the descriptive approach was relied upon. The research community consisted of permanent and collaborating faculty members, numbering (68) individuals, and the number of valid questionnaires for analysis was 31 questionnaires, equivalent to 45% of the research community. Based on the analysis of quantitative data, a set of results were reached, the most prominent of which were: the existence of a positive correlation between the dimensions of information and communication technology, and that the most important dimensions were the software and human resources dimensions with a high degree, the participants’ answers were close to the rest of the dimensions (databases, communication networks, devices and equipment), and they all came with a medium degree of importance. A set of recommendations were proposed, the most important of which are: focusing on the use of information and communication technology through interest in human resources, devices and equipment, databases, software, and communication networks, which would achieve many advantages for the academy. It requires interest in training and attracting expertise and capabilities that deal with technology, providing sufficient requirements and capabilities of devices and equipment and developing current databases to serve the educational process, avoiding reliance on traditional methods and routine work in managing the academy and replacing them with modern methods in managing administrative work.